HUMAN-MACHINE INTERACTION IN SOLVING TASKS OF THE PLANNING DEPARTMENT - Boris Alekseyevich Kucherov; Vladimir Mikhailovich Artyushenko (Acta Polytechnica CTU Proceedings, 2017)
The paper discusses issues of human-machine interaction in solving tasks of the planning department under severe resource restrictions using information technology. The negative factors influencing specialists of the planning department in solving their tasks under the given circumstances are shown. Specific features of designing the user interface in this subject area are noted. Directions to increase the efficiency of reaction of the planning department’s specialists to change the current situation by visual and sound notification of various events are marked. Various ways to develop user interface to generate a conflict-free plan under severe resource restrictions are considered. The variants of informative presentation of operational and statistical information to stakeholders are analyzed. These issues are discussed by the example of the planning department which solves the tasks of allocation of control facilities for spacecraft (a subset of satellite range scheduling problem),